Pengaruh Online Consumer Review terhadap Minat Beli melalui Virtual Hotel Operator - Adisa Dini Anggraeni; Marcellia Susan (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
Budget hotel is predicted to be one of the largest market shares in South Asian Market’s hospitality sector, which leads to the birth of Virtual Hotel Operators (VHO), an online platform which specifically offers for budget hotels accommodation. As VHO becomes one of the platforms to be used to book budget hotels online, people are often finding previous comments consumer to consult. Therefore, this research aims to see the influence of Online Consumer Review Dimension towards Purchase Intention via one of VHOs in Indonesia. This research uses descriptive quantitative approach, the data is collected through questionnaire from google form, there were 107 respondents’ chosen using judgmental sampling. The hypothesis testing is done using multiple regressions, using Valence, Volume and Timeliness of Online Consumer Review as independent variable and Hotel Booking Intention as dependent variable. The result shows that Valence, Volume and Timeliness of Online Consumer Review simultaneously influence Hotel Booking Intention through VHO. Meanwhile, only Timeliness influences Hotel Booking Intention through VHO partially. To sum up, the Online Consumer Review is still used as reference before booking hotel online through VHO. Particularly, the Timeliness is quite important, since it could give the timely description about the hotels.